Apixaban for Primary Prevention of Venous Thromboembolism in Patients With Multiple Myeloma Receiving Immunomodulatory Therapy - Cornell, Robert Frank; Goldhaber, Samuel Z.; Engelhardt, Brian G.; Moslehi, Javid; Jagasia, Madan; Patton, Daryl; Harrell, Shelton; Hall, Robert; Wyatt, Houston; Piazza, Greg (Frontiers in Oncology, 2019)
Immunomodulatory drugs (IMiDs), including thalidomide, lenalidomide, and pomalidomide, have improved survival of patients with multiple myeloma (MM). However, these therapies are associated with an increased risk of venous thromboembolism (VTE). Apixaban has been approved for treatment of acute VTE and for risk reduction of recurrent VTE following initial therapy. In this phase IV ingle-arm study (NCT02958969), we aim to prospectively evaluate the safety and efficacy of apixaban for primary prevention of VTE in patients with MM. The primary efficacy objective of this trial is to determine the rate of symptomatic VTE, including deep vein thrombosis (DVT) and pulmonary embolism (PE), over 6 months. The primary safety objective is to determine the rate of major bleeding in MM patients receiving apixaban prophylaxis. If proven safe and effective, apixaban will emerge as a promising option for oral VTE prophylaxis in MM patients.